2014 IEEE 21st Symposium on Communications and Vehicular Technology in the Benelux (SCVT) 2014
DOI: 10.1109/scvt.2014.7046702
|View full text |Cite
|
Sign up to set email alerts
|

Single-tone interference in noise-based frequency offset modulation

Abstract: A noise-based frequency offset modulation (N-FOM) system is studied in the presence of a single-tone interferer. A closed-form expression for the signal-to-noise ratio is derived and the asymptotic limit of the performance is calculated. The results show that by choosing a suitable value of the frequency offset, the N-FOM system can have an acceptable performance in the presence of single-tone interference, particularly in comparison with modulated interference. However, due to the self-correlation operation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The TR system using noise-based frequency-offset modulation (N-FOM) has been investigated in [14]- [17]. The research in [15] and [16] shows robustness of the N-FOM system against narrowband interferences for low-to-moderate signal-to-interference ratios. In [17], the N-FOM system is investigated in dense frequency-selective channels, where it is shown that a communication link with acceptable error rate can be established in certain channel environments.…”
Section: Introductionmentioning
confidence: 99%
“…The TR system using noise-based frequency-offset modulation (N-FOM) has been investigated in [14]- [17]. The research in [15] and [16] shows robustness of the N-FOM system against narrowband interferences for low-to-moderate signal-to-interference ratios. In [17], the N-FOM system is investigated in dense frequency-selective channels, where it is shown that a communication link with acceptable error rate can be established in certain channel environments.…”
Section: Introductionmentioning
confidence: 99%
“…TR modulation consumes higher power than a general modulation technique to transmit individual bits, since the reference signal is also sent [7]. Furthermore, the receiver has a performance penalty because of the self-mixing of the modulated as well as the unmodulated signal and the interfering signals of multiple frequency offsets using the same spectrum [16,17,15]. As a result, achieving energy-efficiency in the upper MAC layer is crucial for TR modulation.…”
Section: Research and Design Challengesmentioning
confidence: 99%
“…However, TR modulation has a power penalty in the transmitter because of sending the reference signal together with the modulated signal, which accounts for 3 dB power penalty [7]. Furthermore, the cross-mixing of the received signal increases the overall noise-floor at the receiver, which further increases the overall power penalty in TR modulation to 10.7 dB [16,17]. Therefore, an energy-efficient MAC layer protocol customized to the TR modulation is necessary to exploit all the advantages provided by the TR modulation, while minimizing its drawbacks.…”
Section: Motivationmentioning
confidence: 99%